Grounded Theory in preschool. Gender and STEM: an exploratory study - Buccini, Francesca (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2024)
The research reported in the paper has as its objective the study and analysis of the issue of the gender gap in science (STEM) courses at pre-school level and presents the results of a qualitative investigation (grounded theory) involving more than 20 teachers. The specific group of professionals involved acts as a support to restore meaning to the educational experience and to extract precisely from the context explored the elements of a design capable of intercepting critical issues and tracing trajectories of awareness for an educational culture capable of acting on changes and gender prejudices precisely from the quality of everyday practice.